(untitled) (Experimental biology, 2015)
Adaptation of students to educational activity is reflected in a functional condition of an organism. Decrease in of blood circulation at performance of the dosed out functional loading is revealed. Muscular work of moderate capacity in a combination to resistive loading causesa number of essential changes of indicators of respiratory system.